Oxide Microelectronics: Monolithically Integrated Circuits from Functional Oxides (Adv. Mater. Int. 1/2014). Issue 1 (February 2014) - Jany, Rainer; Richter, Christoph; Woltmann, Carsten; Pfanzelt, Georg; Förg, Benjamin; Rommel, Marcus; Reindl, Thomas; Waizmann, Ulrike; Weis, Jürgen; Mundy, Julia A.; Muller, David A.; Boschker, Hans; et al.
<x xml:space="preserve">Abstract</x> The cover displays an optical microscopy image (interference contrast) of a monolithically integrated all‐oxide NMOS chip, showing sections of five ring‐oscillators. The field effect transistors of these integrated circuits are based on the conducting, twodimensional electron liquid formed at LaAlO3/SrTiO3 interfaces. This work, reported in article 1300031 by R. Jany and co‐workers, represents a breakthrough in oxide electronics. Providing the capability to actively process the signals of oxide devices such as sensors on‐chip, these results illustrate the practicability and the potential of electronics based on functional oxides <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>